Antibiotic Use in Poultry Production in Grenada. (27th June 2019) - Glasgow, Lindonne; Forde, Martin; Brow, Darren; Mahoney, Catherine; Fletcher, Stephanie; Rodrigo, Shelly
Abstract : Objective . Research is often lacking in low-income countries to substantiate the regulation of antibiotics in poultry production. Nonregulation of antibiotics in food animal industries has implications for human health. This study was conducted to provide an understanding of farmers' knowledge, attitudes, and practices regarding the use of antibiotics in poultry production in Grenada. Method . A cross-sectional study was conducted in August-September, 2016, surveying 30 poultry farmers each having 500 or more chickens grown for commercial purposes. Results . More than 1000 birds were kept on 18 (60.0%) farms. Antibiotics were used on the majority of farms (25, 83.3%). More than half of the respondents, 19 (63.3%), stated they were only somewhat aware of issues related to the use of antibiotics and the majority, 21 (70.0%), were also unable to define antimicrobial resistance. There was inconsistency in the farmers' knowledge about how and when to use antibiotics. There was also a high level of noncompliance with manufacturers' recommendations for use of antibiotics. The respondents were not aware of local programs to monitor antibiotic use or manage antibiotic resistance in the poultry industry. Conclusion . Generally, the farmers' knowledge and practices were inconsistent with recommendations by the World Health Organization for antibiotic stewardship. While low-income countries, such as Grenada, are challenged with the lack of resources to undertake research and implement responsive actions, this research highlights the need for some immediate measures of remedy, such as education of farmers and monitoring procurement and use of antibiotics, to reduce risk to public health.